(untitled) (Research, Society and Development, 2021)
The objective was to evaluate the yield of tambaqui fillet submitted to different filleting methods. The experimental design was completely randomized, with three filleting methods and nineteen repetitions. The treatments were based on the removal or not of the head and fins of the fish before the filleting process and on the way to remove the skin, before or after the removal of the fillet. The tambaqui had an average weight of 2620.81 g, total length of 50.17 cm, standard length of 40.26 cm, body width of 19.32 cm. The filleting methods in tambaqui significantly influenced (P <0.05) the weight of the skinless fillet, skinned fillet, raw skin, clean skin, carcass, head, total residues. The PIVF filleting method showed greater weight of the skinless fillet, skinned fillet, raw skin, clean skin, carcass, total residues, but did not differ significantly from the PDEF filleting method. The filleting methods evaluated did not significantly influence (P> 0.05) the yield of skinless fillet, skinned fillet, raw skin, clean skin, carcass and total waste. The filleting method with PIVF is recommended for the fish industry for the use of residues, as it presents a greater volume of residues with low-cost raw material potential for the generation of new products. The PDEN filleting method is the most suitable when the processing industry does not allocate waste for reuse.